Pengaruh Media Berbasis Argument Mapping Terhadap Kemampuan Pemahaman Konsep Siswa Kelas V Pada Pelajaran Pancasila - Juniar Afisa; Misrina; Nuraini (STAI AL-AMIN, 2026)
Civic education in elementary schools plays an important role in shaping character and understanding of Pancasila values. However, learning methods that still predominantly use lectures often make it difficult for students to understand abstract concepts. This study was conducted to test the urgency of using Argument Mapping-based media as an innovative alternative in improving students' conceptual understanding. The study used a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 35 fifth-grade students at SD Negeri 3 Blang Mangat, divided into an experimental class (18 students) using Argument Mapping and a control class (17 students) using conventional methods. The instrument was an essay test consisting of 8 items that had been tested for validity and reliability. The results showed a significant increase in the experimental class (average 72.22 to 91) compared to the control class, with a t-test (p < 0.05) proving a positive effect. It was concluded that the Argument Mapping media was effective in improving students' conceptual understanding and training them to think critically, systematically, and logically.